2017
DOI: 10.1002/ijc.30877
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PD‐1 upregulation on tumor‐infiltrating lymphocytes in human and murine gliomas and preclinical therapeutic blockade

Abstract: Blockade of the immune checkpoint molecule programmed-cell-death-protein-1 (PD-1) yielded promising results in several cancers. To understand the therapeutic potential in human gliomas, quantitative data describing the expression of PD-1 are essential. Moreover, due the immune-specialized region of the brain in which gliomas arise, differences between tumor-infiltrating and circulating lymphocytes should be acknowledged. In this study we have used flow cytometry to quantify PD-1 expression on tumor-infiltratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
(75 reference statements)
2
19
0
Order By: Relevance
“…To characterize the immune exhaustion profile of GBM TILs in comparison with PBLs, we analyzed the following markers: PD-1, Tim-3, KLRG1, CD57, CD39, and CD73. PD-1 proved to be the most strikingly upregulated exhaustion marker on both CD8 þ and CD4 þ TILs, which is in line with a recently published study (40). Expanding on those previous findings, we further demonstrate a significant increase of PD-1 expression on PBLs in patients with rGBM versus patients with pGBM, suggesting an even more pronounced systemic exhaustion in the relapse setting.…”
Section: Discussionsupporting
confidence: 91%
“…To characterize the immune exhaustion profile of GBM TILs in comparison with PBLs, we analyzed the following markers: PD-1, Tim-3, KLRG1, CD57, CD39, and CD73. PD-1 proved to be the most strikingly upregulated exhaustion marker on both CD8 þ and CD4 þ TILs, which is in line with a recently published study (40). Expanding on those previous findings, we further demonstrate a significant increase of PD-1 expression on PBLs in patients with rGBM versus patients with pGBM, suggesting an even more pronounced systemic exhaustion in the relapse setting.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the results in the clinic with checkpoint inhibitors for GBM, treatment of mice bearing 005 GSC-derived tumors, representative of immunologically 'cold' tumors, with systemic immune checkpoint antibodies (anti-PD-1 or anti-PD-L1 or anti-CTLA-4) provided only modest prolongation of survival [17]. This contrasts with the results seen with mouse GL261 syngeneic tumors [47][48][49]. Even the combination of two antibodies (anti-PD-1+anti-CTLA-4) was not successful in the 005 GSC model, only delaying tumor progression without cures [17].…”
Section: Immune Checkpointsmentioning
confidence: 60%
“…In this study, we studied not only which immune checkpoint receptors are expressed on CD8 þ TILs in patients with GBM, but also whether their proliferation can be restored by blocking immune checkpoint receptors. Previous studies have shown increased expression of PD-1 (33)(34)(35)(36), Tim-3 (35)(36)(37), and LAG-3 (36) on CD8 þ TILs in patients with GBM; however, to the best of our knowledge, ex vivo functional assays to reinvigorate CD8 þ TILs by ICI treatment have not yet been performed in GBM.…”
Section: Discussionmentioning
confidence: 95%